The effect of continuous rectangular spiral shear reinforcement on the dynamic behavior of RC solid slab subjected to low-velocity impact loading - Al-Dala'ien R.N. (Elsevier B.V., 2025)
This study investigates the effect of continuous rectangular spiral shear reinforcement on reinforced concrete slabs under low-velocity conditions, crucial for scenarios such as landslides or vehicular collisions. By combining experimental and finite element analyses using ABAQUS, this research assesses the effectiveness of this reinforcement method. The experimental setup involves subjecting slabs to impact loading with consistent energy levels using a drop weight system. Various parameters, including acceleration time, strain-time in steel and concrete, and failure mode, are carefully monitored throughout the study. Results demonstrate a notable 216.13% improvement in energy absorption and a 43.70% increase in impact ductility compared to control specimens, reflecting higher rigidity and stiffness in spiral-reinforced specimens, as evidenced by elevated maximum acceleration values. Specimens with continuously rectangular spirals exhibit less severe surface damage upon complete failure, emphasizing their enhanced impact resistance. Diagonally arranged spiral reinforcements notably reduce damage, displacement, and stress. These findings highlight the significant potential of continuously rectangular spirals in improving the low-velocity behavior of reinforced concrete slabs, offering valuable insights for structural design and reinforcing systems. Additionally, using ABAQUS finite element analysis validates experimental findings, providing efficient insights into structural behavior under dynamic conditions. ? 2024 The Authors